Coupling effects of manufacturing error and flexible ring gear rim on dynamic features of planetary gear. (November 2021) - Cao, Zheng; Rao, Meng
Manufacturing errors widely exist in and deteriorate the dynamic property of planetary gear train (PGT). To solve this problem, the ring gear is often designed with a thin rim to compensate for the effects of manufacturing errors via the elastic deflections of the rim. Existing dynamic models of the PGT only consider the effects of either the elasticity of the rim of the ring gear or the manufacturing errors. The coupling effects of manufacturing errors and the flexible ring gear are ignored. To understand the dynamic behaviors of the PGT better, a dynamic model of the PGT coupled with typical manufacturing error and flexible ring gear is developed in this study. The tooth contact analysis of the ring-planet mesh, which is calculated based on the potential energy method and uniformly curved Timoshenko beam theory, is studied using the influence coefficient method. A numerical algorithm is proposed to solve the integrated dynamic equations of the PGT. Calculated results show that the dynamic features of the PGT are complex, and the load sharing characteristic is improved when the flexible ring gear is incorporated.